2016
DOI: 10.5301/ijao.5000544
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Infantile Arterial Calcification: A Case Report of Successful Extracorporeal Membrane Oxygenation Support

Abstract: Idiopathic infantile arterial calcification is a rare cause of infantile ischemic cardiac failure with extremely poor prognosis. We present the first case report of successful extracorporeal membrane oxygenation support and outcome in a child with idiopathic infantile arterial calcification (IIAC). This 6-week-old infant presented with cardiogenic shock and circulatory collapse. The patient underwent extracorporeal cardiopulmonary resuscitation, allowing stabilization, diagnosis, and treatment with etidronate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In a previously published article, neurologic manifestations were reported in patients with GACI, with magnetic resonance imaging (MRI) proved strokes, gliosis, bilateral occipital necrosis, and cystic encephalomalacia ( 2 ) but no histopathological findings were shown. As miscarriage, hydrops, polyhydramnios, and fetal distress were seen in our and other reported cases ( 3 , 19 ), it can be supposed that GACI might be a favoring factor rather than a consequence of intrauterine infections. On the other hand, in the present case, the mother's paraclinical tests indicated high serum values for anti-CMV IgG and anti- T. gondii IgG, but not for the IgM.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In a previously published article, neurologic manifestations were reported in patients with GACI, with magnetic resonance imaging (MRI) proved strokes, gliosis, bilateral occipital necrosis, and cystic encephalomalacia ( 2 ) but no histopathological findings were shown. As miscarriage, hydrops, polyhydramnios, and fetal distress were seen in our and other reported cases ( 3 , 19 ), it can be supposed that GACI might be a favoring factor rather than a consequence of intrauterine infections. On the other hand, in the present case, the mother's paraclinical tests indicated high serum values for anti-CMV IgG and anti- T. gondii IgG, but not for the IgM.…”
Section: Discussionsupporting
confidence: 73%
“…Untreated, death of the infant occurs before the age of 6 months by myocardial ischemia and cardiorespiratory arrest ( 6 , 19 ). In any baby with pulmonary hypertension and hydramnios, GACI should be suspected ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deshpande et al published the first report of successful mechanical support in a patient with GACI, additionally, over time with bisphosphonate therapy, there was a remarkable recovery of cardiac function ( 46 ). Giovannoni et al reported an 18-month-old child with GACI and end-stage myocardial ischemia who underwent successful heart transplantation ( 47 ).…”
Section: Discussionmentioning
confidence: 99%